Chlamydia pneumoniae Influence on Cytokine Production in Steroid-Resistant and Steroid-Sensitive Asthmatics - Dóra Paróczai; Tímea Mosolygó; Dávid Kókai; Valéria Endrész; Dezső P. Virok; Attila Somfay; Katalin Burián (Pathogens, 2020)
Medications for asthma management consisting of inhaled corticosteroids act by controlling symptoms. However, some patients do not respond to steroid treatment due to immunological factors at the cytokine level. Chlamydia pneumoniae (C. pneumoniae) infection is strongly implicated in asthma pathogenesis, causing altered immune responses. We investigated the association of C. pneumoniae serostatus with the production of certain cytokines by peripheral blood mononuclear cells (PBMCs) of steroid-resistant and -sensitive asthmatic patients. Our most important findings are the following: In the case of C. pneumoniae seropositive patients we detected pronounced spontaneous interleukin (IL)-10 secretion and, in the case of steroid-resistant patients, IL-10 secretion was at a significantly higher level as compared with in-sensitive patients (p < 0.01). Furthermore, steroid-resistant seropositive patients produced a significantly higher level of IL-10 spontaneously and under antigen stimulation as compared with steroid-resistant seronegative individuals (p < 0.05). Concerning spontaneous TNF-α secretion by C. pneumoniae seropositive asthmatics, we observed that steroid-resistant patients produced significantly more of this cytokine than steroid-sensitive patients. In the steroid-resistant patients’ sera, a remarkably high MMP-9 concentration was associated with C. pneumoniae seronegativity. Our study revealed that the differences in the cytokine production in steroid-sensitive and -resistant asthmatic patients can be influenced by their C. pneumoniae serostatus.